Frenulum Protection Technique in Disposable Circumcision Suture Device for Adult Males - Lu, Xiaojun; Piao, Shuguang; Qin, ShenFei; Zhang, KaiXuan; Li, JiaCheng; Zhou, WenHao; Tang, Lei; Yan, Shi; Chen, Yuangui; Yin, Guonan; et al. (Urology Journal, 2023)
Purpose: To evaluate the efficacy of frenulum protection technique of the disposable circumcision suture device (DCSD) in adult males. Materials and Methods: Atotal of 53 adult males were diagnosed with redundant prepuce and underwent circumcision with DCSD using frenulum protection technique. The main preoperative and postoperative measure of the length of penile frenulum was evaluated. Other data such as edema rate, intraoperative blood loss, operation time, postoperative pain, staple falling off time, incision infection rate, and evaluation of satisfaction rate with penis appearance were documented in the study. Results: There was no significant difference in preoperative and postoperative frenulum length for each patient. The mean length of the penile frenulum before and after surgery was 2.25 ± 0.36 cm and 2.23 ± 0.39 cm, respectively (p = .31). The rate of frenulum length preservation was 100%. All the patients had no excessive resection of the frenulum and no serious complication happened after surgery. The satisfaction rate of postoperative penis appearance from patients’ evaluation was 98.1% (52/53). Conclusion: The frenulum protection technique was simple and operable, which could help the operator to accurately identify the most distal position of the frenulum and retain a sufficient length of frenulum during DCSD circumcision.